CHILD DEVELOPMENT AND SOCIAL SKILL FORMATION:A THEORETICAL REVIEW AND CURRENT SOCIAL PHENOMENA - Meiti Subardhini; Kanya Eka Santi; Rini Hartini Rinda (Adisam Publisher, 2025)
Social skills are an important aspect of children's development that affects their ability to interact, adjust and build healthy interpersonal relationships. This study aims to theoretically and empirically review children's social skills, by highlighting the process of their formation from an early age, the implications of low social skills, and the challenges faced by Generation Z children in the current social context. The method used is a literature review by analyzing various scientific journals, books, and previous research results. The results show that children's social skills are in the moderate category, with assertiveness being the weakest aspect. Factors such as parental education level, parenting, school environment and exposure to digital media play an important role in influencing the formation of social skills. Low social skills result in difficulties in interpersonal relationships, emotional instability, decreased academic performance, and increased social risks such as bullying, isolation and depression. The phenomenon of weak social ethics in some Generation Z reflects a failure in the formation of social values and skills early on. This study emphasizes the importance of synergy between families, schools and communities in strengthening children's social skills through training, character education and policies that support children's social-emotional development. Recommendations are directed at the need for sustainable social interventions and further research related to the effectiveness of social skills training programs in various social and cultural contexts.